2018
DOI: 10.1007/s11845-018-1932-9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns were not associated with age-related macular degeneration: a cross-sectional analysis in the Irish Nun Eye Study

Abstract: Background Analysing dietary patterns (DP) evaluates overall dietary intake, taking account of its complexity, quality, variance and the interaction between different foods, providing an alternative approach for the evaluation of nutritional influences on agerelated macular degeneration (AMD) risk. Aims To evaluate the relationship between DP and AMD in an older female population. Methods Data was analysed from the cross-sectional Irish Nun Eye Study involving 1233 older women with a restricted lifestyle (mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…However, it was reported that the Western pattern may be a risk factor for the development of late AMD (267) . Similar to this study, the Irish Nun Eye Study observed no association between a diet model and the risk of AMD (268) . The complexity of DP composition, geographic variations in dietary intake, genetic factors and AMD definitions can be confounding factors limiting the association between diet and AMD outcomes.…”
Section: Dietary Patternssupporting
confidence: 84%
See 2 more Smart Citations
“…However, it was reported that the Western pattern may be a risk factor for the development of late AMD (267) . Similar to this study, the Irish Nun Eye Study observed no association between a diet model and the risk of AMD (268) . The complexity of DP composition, geographic variations in dietary intake, genetic factors and AMD definitions can be confounding factors limiting the association between diet and AMD outcomes.…”
Section: Dietary Patternssupporting
confidence: 84%
“…The complexity of DP composition, geographic variations in dietary intake, genetic factors and AMD definitions can be confounding factors limiting the association between diet and AMD outcomes. The low prevalence of AMD in the Irish Nun Eye study population, their relatively good health for their age, and their restricted dietary intake may have limited the statistical power to detect an association between diet and AMD (268) . The presence of certain factors, such as variations in geographic dietary patterns, genetic variations, and differences in how AMD is classified, could introduce confusion and limit the ability to detect clear associations with dietary outcomes.…”
Section: Dietary Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with high genetic risk, weekly fish consumption was associated with a 40% lower risk of late AMD (Wang et al 2014). In contrast, three studies demonstrated no effect of regular fish intake on the risk of AMD (Nano et al 2013;Ersoy et al 2014;McCarter et al 2018). Another study observed that the consumption of fish was not different between patients with AMD and healthy controls (Gopinath et al 2017).…”
Section: Effects Of Marine Resources On Retinal Disease Prevalence and Severitymentioning
confidence: 97%
“…Not all prudent dietary patterns have shown protective associations against AMD. A smaller study of the Irish Nun Eye Study identified a healthy dietary pattern containing fruits, vegetables, oily fish, nuts, and several other foods, but did not identify associations with AMD for any of their dietary patterns [ 16 ]. Notably, the healthy dietary pattern also included red meat and pizza, suggesting that, like in the Rotterdam Eye study dietary pattern analysis, protection from AMD may have as much to do with what is not consumed, as what is consumed.…”
Section: Dietary Patterns and Eye Diseasementioning
confidence: 99%